Enhancing tailing quality with Pistia stratiotes as an ameliorant for sustainable crop cultivation: a case study using fruit vegetable - Taberima, Sartji; Prabawardani, Saraswati; Mawikere, Nouke L.; Fenetiruma, Obadja A.; Luhulima, Fiona Djunita Natalia; Ubra, Emillia Farida (Brawijaya University, 2025)
Tailing land reclamation aims to enhance the environment and improve the condition of tailing land, transforming it into more productive areas suitable for plant cultivation. This study examined the utilization of tailings (residues from PT Freeport Indonesia's mining product processing activities) in tomato cultivation. The research was conducted at Mile 21.5, Timika, from March to September 2022. The primary objective was to evaluate the improvement of tailing quality for crop cultivation, as reflected by the growth and yield of tomatoes, using Pistia stratiotes compost as an ameliorant. The experiment was designed using a Randomized Block Design (RBD) approach, comprising five levels of compost dosage (PS 0 = 0 kg/plant, PS 1 = 1 kg/plant, PS 2 = 2 kg/plant, PS 3 = 3 kg/plant, and PS 4 = 4 kg/plant), with six replications per treatment. The analysis demonstrated a significant enhancement in tailing quality, as indicated by the increased soil nutrient concentrations after the application of Pistia stratiotes compost. Moreover, the treatment had a significant positive effect, with tomato plants receiving the ameliorant exhibiting higher productivity compared to those without treatment.